Composite material as well as preparation method and application thereof
By using the phosphorus-carbon composite material with porous carbon skeleton and carbon-clad layer structure in lithium-ion batteries, the problem of poor volume expansion and circulation performance is solved, higher energy density and stability are achieved, and its commercial development is promoted.
Patent Information
- Application Number
- CN202411817684.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing phosphorus-carbon composite materials have severe volume expansion effects and poor circulation performance in lithium-ion batteries, which limits their commercial development.
Using a porous carbon skeleton and a carbon cladding structure, a carbon cladding layer is formed on the surface by attaching nanored phosphorus to the porous carbon skeleton and forming a carbon cladding layer on the surface to slow down volume expansion and control capacity attenuation.
It effectively solves the volume expansion problem, improves cycling performance and conductivity, enhances the stability of the electrode structure, and significantly improves the energy density and commercialization potential of phosphorus-carbon composite materials.
Smart Images

Figure BDA0005182274560000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to composite materials and preparation methods and applications thereof. Background Art
[0002] The theoretical specific capacity of graphite anodes used in commercial lithium-ion batteries is only 372mAh / g, but the theoretical specific capacity of single red phosphorus is as high as 2596mAh / g, which is much higher than the theoretical specific capacity of graphite and second only to silicon. Therefore, red phosphorus is a lithium-ion anode material with abundant reserves, low price, non-toxicity and huge application potential. However, red phosphorus has poor conductivity and, similar to silicon materials, has a volume expansion effect during the charge and discharge process, which has seriously affected its application in lithium batteries.
[0003] To this end, the commonly used solution is to compound red phosphorus with carbon materials by ball milling, sublimation condensation, thermal reduction, chemical precipitation, etc. Although the composite phosphorus-carbon composite material has a high theoretical capacity, the serious volume expansion effect is still unavoidable, and the cycle performance is poor, which greatly limits its commercial development. Therefore, it is necessary to provide a phosphorus-carbon composite material with excellent comprehensive performance, which can slow down expansion, control capacity decay, and improve cycle stability. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a composite material with small volume expansion and good cycle performance, and a preparation method and application thereof.
[0005] In a first aspect of the present application, a composite material is provided, the composite material comprising:
[0006] A porous carbon framework, wherein nano red phosphorus is attached to the porous carbon framework;
[0007] The carbon coating layer is coated on the surface of the porous carbon skeleton.
[0008] The composite material according to the first aspect of the present application has the following beneficial effects:
[0009] The porous carbon skeleton has a large number of pores, which can effectively solve the volume expansion problem of the nano red phosphorus attached to it, shorten the electron transmission distance, accelerate the electron transfer and the insertion and extraction of cations in it, and the transmission between the electrode and the electrolyte interface. The outer carbon coating layer can isolate the nano red phosphorus in the carbon skeleton and the phosphate salt generated under working conditions from direct contact with the electrolyte to avoid the occurrence of side reactions; it can also improve the conductivity of the material, reduce polarization, and ensure the stability of the electrode structure. Therefore, the composite material can bring excellent cycle performance as a negative electrode active material.
[0010] In some embodiments of the present application, the porosity of the porous carbon skeleton is greater than 40%, for example, it may be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or more.
[0011] In some embodiments of the present application, the mass percentage of nano red phosphorus in the porous carbon skeleton is more than 50%, for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80% or more.
[0012] In some embodiments of the present application, the raw material of the porous carbon skeleton includes at least one of graphite and hard carbon.
[0013] In some embodiments of the present application, the graphite includes at least one of single particles and secondary particles.
[0014] In some embodiments of the present application, the graphite includes at least one of artificial graphite and natural graphite.
[0015] In some embodiments of the present application, the composite material satisfies 0.1<7a 2 b / (10(1-a) 2 ×c×d)<1.1; wherein a is the mass percentage of the nano red phosphorus in the porous carbon skeleton; b is the average particle size D of the nano red phosphorus V 50, in μm; c is the average particle size D of the porous carbon skeleton V 50, in μm; d is the porosity of the porous carbon skeleton. When the nano red phosphorus and the porous carbon skeleton satisfy the above relationship, it can ensure that the composite material has both high capacity and low expansion.
[0016] In some embodiments of the present application, the average particle size D of graphite and hard carbon is V 50 is 100nm~20μm, and can be specifically 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 800nm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, and 10μm.
[0017] In some embodiments of the present application, the average particle size D of nano red phosphorus V 50 is 1 to 1000 nm, and specifically can be 1 nm, 2 nm, 4 nm, 5 nm, 6 nm, 8 nm, 10 nm, 20 nm, 40 nm, 50 nm, 60 nm, 80 nm, 100 nm, 200 nm, 400 nm, 500 nm, 600 nm, 800 nm, 1000 nm. It is understood that, generally, the average particle size D of graphite and hard carbon is V50 is larger than the average particle size D of nano red phosphorus V 50, for example, the former is 2 to 200 times of the latter, specifically 2 times, 3 times, 4 times, 5 times, 6 times, 8 times, 10 times, 15 times, 20 times, 25 times, 30 times, 40 times, 50 times, 60 times, 80 times, 100 times, 150 times, 200 times.
[0018] In some embodiments of the present application, the average particle size D of the porous carbon skeleton is V 50 is 2-50 μm, specifically 2 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm. In some embodiments, the outer surface of the porous carbon skeleton can be, for example, spherical or ellipsoidal.
[0019] In the present application, the average particle size Dv50 refers to the particle size corresponding to 50% volume distribution.
[0020] In a second aspect of the present application, a method for preparing a composite material is provided, the method comprising the following steps:
[0021] S100: mixing red phosphorus, a first carbon source and a self-sacrificial template, pressurizing and heating to 100-200° C. under a protective atmosphere to obtain a mixed solid;
[0022] S200: heating the mixed solid to 250-400° C. to crush the mixed solid to obtain mixed particles;
[0023] S300: mixing the mixed particles with a second carbon source and carbonizing at 420-500° C. to obtain an intermediate;
[0024] S400: Cooling the intermediate to 240-280° C. to obtain a composite material.
[0025] In the above preparation method, red phosphorus, a first carbon source and a template are first mixed, and heated and pressurized to generate a mixed solid with a large number of micro-voids in the mixture to facilitate heating and crushing; the mixed solid is heated and crushed, and a second carbon source is introduced on the surface of the obtained mixed particles, and the first carbon source and the second carbon source are converted into a porous carbon skeleton and a carbon coating layer by a one-time carbonization method, and at the same time, the template agent is pyrolyzed to generate void spaces, and the red phosphorus mixed therein will sublime, and the phosphorus vapor will be adsorbed by the void spaces of the porous carbon skeleton through capillary force and pressure difference to obtain an intermediate; finally, the white phosphorus is converted into nano red phosphorus by cooling, forming a composite material in which nano red phosphorus is distributed in the void spaces of the porous carbon skeleton and the outer surface is covered with a carbon coating.
[0026] In some embodiments of the present application, the self-sacrificial template includes at least one of polystyrene, polymethyl methacrylate, and polyetherimide. The above template can be completely pyrolyzed during the heating process to maximize the void space generated to accommodate more red phosphorus, increase the gram capacity and control the volume expansion.
[0027] In some embodiments of the present application, the first carbon source includes at least one of graphite and hard carbon.
[0028] In some embodiments of the present application, the graphite includes at least one of single particles and secondary particles.
[0029] In some embodiments of the present application, the graphite includes at least one of artificial graphite and natural graphite.
[0030] In some embodiments of the present application, the second carbon source includes at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, melamine resin, polybutadiene resin, polydopamine, citric acid, glucose, fructose, sucrose, maltose, dextrin, starch, sorbitol, tartaric acid, ethylenediaminetetraacetic acid, polyethylene glycol, polyvinyl alcohol, polyvinyl butyral, polyacrylic acid, carboxymethyl cellulose, coal tar pitch, and needle tar pitch.
[0031] In some embodiments of the present application, the pressure condition of the pressurization treatment is 2 to 6 kPa, for example, it can be 2 kPa, 3 kPa, 4 kPa, 5 kPa, or 6 kPa.
[0032] After mixing red phosphorus, the first carbon source and the template, heating and pressurizing, maintaining micro-voids in the mixture, stabilizing and cooling to obtain a mixed solid; the mixed solid is heated at high temperature and then crushed, and then the second carbon source is introduced on the surface of the mixed solid, and the first carbon source and the second carbon source are converted into a carbon skeleton and a coating layer by a one-time carbonization method, while the template is pyrolyzed to produce void space, the carbon skeleton is converted into a porous carbon skeleton, and the red phosphorus inside is sublimated, and the phosphorus vapor is adsorbed by the porous carbon skeleton through capillary force and pressure difference, and then the temperature is reduced to convert the white phosphorus into red phosphorus. Finally, a composite material with nano-red phosphorus distributed on the porous carbon skeleton and a carbon coating on the outer surface is formed.
[0033] According to a third aspect of the present application, a secondary battery is provided. The secondary battery comprises the aforementioned composite material.
[0034] In some embodiments of the present application, the secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, the negative electrode sheet includes a negative electrode collector and a negative electrode active material layer, the raw material of the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes the aforementioned composite material.
[0035] In some embodiments of the present application, the raw material of the negative electrode active material layer also includes at least one of a conductive agent and a binder. The conductive agent includes but is not limited to conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15, SO, etc.), conductive carbon black (such as Super P / SP, Super S, 350G, acetylene black, Ketjen black, etc.), conductive carbon fiber (such as vapor-grown carbon fiber VGCF, carbon nanotube CNT) and graphene, etc. The binder includes but is not limited to at least one of polyvinylidene fluoride PVDF, polytetrafluoroethylene PTFE, carboxymethyl cellulose CMC, styrene-butadiene rubber SBR, polyurethane PU, polyvinyl alcohol PVA, polyvinyl butyral PVB, polyacrylate lithium PAALi, etc.
[0036] In some embodiments of the present application, the negative electrode active material layer includes 70 to 99 wt % of the negative electrode active material, 0.5 to 6 wt % of the conductive agent, and 0.5 to 20 wt % of the binder.
[0037] In some embodiments of the present application, when the negative electrode active material, the conductive agent and the binder are made into the negative electrode active material layer, the negative electrode active material, the conductive agent and the binder are dispersed in a solvent and then coated on the negative electrode current collector, and dried to obtain the negative electrode active material layer.
[0038] In some embodiments of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer.
[0039] In some embodiments of the present application, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate LFP, lithium nickel cobalt manganese oxide NCM, lithium nickel cobalt aluminum oxide NCA, lithium nickel manganese aluminum oxide NMA, lithium titanate LTO, etc.
[0040] In some embodiments of the present application, the raw material of the positive electrode active material layer also includes at least one of a conductive agent and a binder. The conductive agent includes but is not limited to conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15, SO, etc.), conductive carbon black (such as Super P, Super S, 350G, acetylene black, Ketjen black, etc.), conductive carbon fiber (such as VGCF, CNT) and graphene, etc. The binder includes but is not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinyl alcohol, polyvinyl butyral, etc.
[0041] In some embodiments of the present application, the positive electrode current collector and the negative electrode current collector are independently selected from at least one of metal materials including metal foil (such as aluminum foil, silver foil, tin foil, iron foil, titanium foil, nickel foil, copper foil or alloy foil of the above metals), metal mesh (such as aluminum mesh, silver mesh, tin mesh, iron mesh, titanium mesh, nickel mesh, copper mesh or alloy mesh of the above metals).
[0042] In some embodiments of the present application, the positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.
[0043] In some embodiments of the present application, the positive electrode active material layer includes 70 to 99 wt % of the positive electrode active material, 0.5 to 6 wt % of the conductive agent, and 0.5 to 20 wt % of the binder.
[0044] In some embodiments of the present application, the electrolyte may be at least one of a solid electrolyte or an electrolyte.
[0045] In some embodiments of the present application, the positive electrode sheet, the negative electrode sheet, and the separator are formed into a secondary battery by at least one of the following methods, including but not limited to winding and lamination.
[0046] In a fourth aspect of the present application, an electrical device is provided, the electrical device comprising the aforementioned secondary battery.
[0047] Among them, electrical equipment refers to any equipment that can use electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Among them, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles can be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0048] Compared with the prior art, the embodiments of the present application have the following advantages:
[0049] 1) During the preparation process of the composite material, self-sacrificial templates such as polystyrene are used to generate a large number of pores in the first carbon source as the carbon skeleton, which solves the problem of serious volume expansion effect of phosphorus-carbon materials, effectively shortens the electron transmission distance, accelerates electron transfer, Li + / Na + The insertion and extraction of cations in the composites and their transport between the electrode and electrolyte interfaces.
[0050] 2) Since red phosphorus and the first carbon source are first mixed, a mixed solid is synthesized by a pressurized method, more than 50 wt% of red phosphorus can be added during the process, the mixed solid is crushed, and then coated with the second carbon source to form a carbon coating layer, and the red phosphorus is evenly distributed on the porous carbon skeleton by a condensation method. Compared with the low red phosphorus loading in a single condensation method, the energy density of the phosphorus-carbon composite material prepared by the method of the embodiment of the present application is greatly improved.
[0051] 3) The composite material has a higher energy density than hard carbon. Whether used as a negative electrode for lithium or sodium batteries, the gram capacity is more than four times that of hard carbon, and the first efficiency can reach more than 90%, with obvious cost advantages. And as a negative electrode for lithium batteries, it has a moderate compaction density, and the lithium insertion potential of phosphorus is high. Even when charged at a large current, the phosphorus-carbon structure is very stable, safe and reliable, and the lithium-phosphorus compound has a positive effect on the diffusion of lithium ions.
[0052] 4) The outer carbon coating layer can avoid direct contact between phosphorus and the electrolyte, effectively isolating the electrolyte from contact with lithium phosphide or sodium phosphide to avoid side reactions; it can also improve the conductivity of the material, reduce polarization, and ensure the stability of the electrode structure.
[0053] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION
[0054] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.
[0055] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.
[0056] In the description of this application, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, "above", "below", "within", etc. are understood to include the number itself, and "about" means within the range of ±20%, 10%, 8%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.2%, 0.1%, etc. of the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0057] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0058] The present application is described below in conjunction with specific embodiments.
[0059] Example 1
[0060] This embodiment provides a composite material, including a porous carbon skeleton and a carbon coating layer coating the porous carbon skeleton, and nano red phosphorus is attached to the surface and internal pores of the porous carbon skeleton.
[0061] The preparation method of the composite material is as follows:
[0062] (1) Take 54 kg of red phosphorus (D v 50 is 800nm), 30kg single-grain graphite (D v 50 (7 μm) and 10 kg of polystyrene were added into the reactor and stirred evenly.
[0063] (2) The reactor was evacuated and heated to 150° C., and then nitrogen was introduced and pressurized to 4 kPa. The temperature was maintained for 4 h to stabilize the microvoids generated in the mixture, and then the temperature was cooled to room temperature to obtain a mixed solid.
[0064] (3) Grind the mixed solid into D v 50 is a mixed particle of 10 μm.
[0065] (4) 6 kg of phenolic resin was dissolved in ethanol, and then added to the mixed particles, stirred at room temperature for 5 h, and then heated to 80° C. to remove the solvent. After drying, the mixture was cured at 100° C. for 1 h in a nitrogen atmosphere, and then heated to 500° C. at a rate of 2° C. / min for carbonization for 5 h to obtain an intermediate containing a porous carbon skeleton and a carbon coating layer containing adsorbed white phosphorus.
[0066] (5) The intermediate is cooled to 260° C. to convert the white phosphorus adsorbed in the porous carbon skeleton into nano red phosphorus, thereby obtaining a composite material.
[0067] The mass fraction of nano red phosphorus in the porous carbon skeleton is 54 / (54+30)×100%=64.3%, and the porosity of the porous carbon skeleton is 60%.
[0068] In this embodiment, 7a 2 b / (10(1-a)2 ×c×d)=7×0.643 2 ×0.8÷(10×(1-0.643) 2 ×7×0.6)=7×0.643 2 ×0.8÷5.35=0.43.
[0069] Example 2
[0070] This embodiment provides a composite material, and the difference between its preparation method and that of embodiment 1 is that the amount of red phosphorus added is 36 kg, and the mass fraction of nano red phosphorus in the porous carbon skeleton is 54.5%.
[0071] In this embodiment, 7a 2 b / (10(1-a) 2 ×c×d)=7×0.545 2 ×0.8÷(10×(1-0.545) 2 ×7×0.6)=7×0.545 2 ×0.8÷8.7=0.19.
[0072] Example 3
[0073] This embodiment provides a composite material, and the difference between its preparation method and that of embodiment 1 is that the amount of red phosphorus added is 84 kg, and the mass fraction of nano red phosphorus in the porous carbon skeleton is 73.7%.
[0074] In this embodiment, 7a 2 b / (10(1-a) 2 ×c×d)=7×0.737 2 ×0.8÷(10×(1-0.737) 2 ×7×0.6)=7×0.737 2 ×0.8÷2.91=1.05.
[0075] Comparative Example 1
[0076] This comparative example provides a composite material, and its preparation method is different from that of Example 1 in that the addition of phenolic resin is omitted, and the mixed particles are directly subjected to pyrolysis reaction after being obtained.
[0077] Comparative Example 2
[0078] This comparative example provides a composite material, and the preparation method thereof is different from that of Example 1 in that the addition of polystyrene is omitted.
[0079] The porosity of the porous carbon skeleton is 20%, 7a 2 b / (10(1-a) 2 ×c×d)=7×0.643 2×0.8÷(10×(1-0.643) 2 ×7×0.2)=7×0.643 2 ×0.8÷1.78=1.3.
[0080] Comparative Example 3
[0081] This comparative example provides a composite material, and its preparation method is different from that of Example 1 in that the red phosphorus in the original step (1) is crushed in step (3) by steam condensation to form mixed particles, and then mixed with phenolic resin for coating. The process of the red phosphorus mixing reaction is as follows:
[0082] 54 kg of red phosphorus powder washed with deionized water and the mixed particles were sealed in an argon-filled reactor and ground for 2 h, then heated to 500 ° C at a rate of 5 ° C / h and maintained for 4 h, and then cooled to 300 ° C and maintained for 20 h to complete the condensation process. After cooling to room temperature, the product was collected, washed with carbon disulfide to remove residual white phosphorus, and dried in a vacuum oven at 60 ° C for 12 h.
[0083] Comparative Example 4
[0084] This embodiment provides a composite material, and the preparation method thereof is different from that of embodiment 1 in that red phosphorus is not added in step (1).
[0085] Comparative Example 5
[0086] This embodiment provides a composite material, and the preparation method thereof is different from that of Embodiment 1 in that no graphite is added in step (1).
[0087] The composite materials of Examples 1 to 3 and Comparative Examples 1 to 5 were respectively used as negative electrode active materials to prepare and assemble batteries. The specific process is as follows:
[0088] 1. Preparation of negative electrode
[0089] The negative electrode active material, conductive agent (SP and CNT mixed in a mass ratio of 9:1), and binder (SBR and PAALi mixed in a mass ratio of 0.5:1.8) were mixed in a mass ratio of 97.7:1.1:1.2 to prepare a negative electrode active material slurry, which was then evenly coated on the negative electrode current collector copper foil, and then cold pressed and slit to obtain a negative electrode sheet.
[0090] 2. Preparation of positive electrode
[0091] The positive electrode active material NCM523, the conductive agent acetylene black, and the binder PVDF were mixed in a mass ratio of 97:2:1, and the solvent NMP was added. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a positive electrode active material slurry. The positive electrode active material slurry was evenly coated on the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0092] 3. Preparation of Electrolyte
[0093] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0094] 4. Choice of diaphragm: Choose polyethylene film as the diaphragm.
[0095] 5. Preparation of Lithium-ion Batteries
[0096] The positive electrode sheet, isolation film and negative electrode sheet are stacked in order, so that the isolation film is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained, with a battery capacity of 5000mAh and a designed 1C=5000mA.
[0097] The prepared lithium-ion batteries were subjected to the following tests:
[0098] (1) Capacity retention rate and thickness expansion rate test:
[0099] S1. Discharge the battery at 0.2C to 3V and leave it for 5 minutes.
[0100] S2. Charge the battery to 4.5V at 0.5C at 25°C with a cut-off current of 0.05C and leave it for 5 minutes.
[0101] S3. Measure the discharge capacity of the battery at this time, recorded as D 前 ; Measure the thickness of the battery at this time, recorded as d 前 .
[0102] S4. Discharge the battery at 0.2C to 3V and leave it for 5 minutes.
[0103] S5. Charge the battery to 4.5V at 1.5C with a cut-off current of 0.05C and leave it for 5 minutes.
[0104] S6. After repeating the above steps S1 to S4 300 times, measure the discharge capacity of the battery at this time, recorded as D后 ; Measure the thickness of the battery at this time, recorded as d 后 ;
[0105] Capacity retention rate after 300 cycles = D 后 / D 前 ×100%;
[0106] Thickness expansion rate after 300 cycles = (d 后 -d 前 ) / d 前 ×100%.
[0107] (2) Gram capacity test:
[0108] Assemble the button battery for testing. The positive and negative electrodes and separator of the button battery are the same as the above-mentioned soft-pack battery. The model of the button battery is 2025. First, discharge the battery to 5mV with a constant current of 0.1mA and let it stand for 10 minutes. Then discharge it to 5mV with a constant current of 0.05mA and let it stand for 10 minutes. Then charge it to 2.0V with a constant current of 0.1mA. Record the charging capacity and calculate the gram capacity and first efficiency according to the following formula:
[0109] Gram capacity = charging capacity / mass of composite material on negative electrode sheet;
[0110] First efficiency = first discharge capacity / first charge capacity × 100%.
[0111] The results are shown in Table 1:
[0112] Table 1. Performance test results of examples and comparative examples
[0113]
[0114] By comparing Example 1 with Comparative Example 1, although the carbon coating layer formed by adding phenolic resin causes a decrease in gram capacity, it can effectively isolate the contact between nano red phosphorus and the electrolyte, avoid side reactions, and significantly improve the first effect and cycle performance.
[0115] Comparing Example 1 and Comparative Example 2, adding a polystyrene template agent for pyrolysis produces a large number of pores in the carbon skeleton, which solves the serious volume expansion effect of the phosphorus-carbon negative electrode material and greatly reduces the cycle thickness expansion rate.
[0116] Comparing Example 1 and Comparative Example 3, when the conventional steam condensation method is used for preparation, red phosphorus is attached to the surface of graphite after being crushed, and the loading amount of red phosphorus is low, and the improvement of gram capacity is limited.
[0117] Comparing Examples 1 to 3 with Comparative Example 4, the phosphorus-carbon negative electrode material prepared by this method has little effect on the cycle capacity retention rate and thickness expansion rate relative to the pure graphite system, but the gram capacity is significantly improved.
[0118] Comparative Example 1 and Comparative Example 5, graphite is used as a carrier to act as a container for loading red phosphorus, thereby reducing expansion and playing a framework role for the entire phosphorus-carbon negative electrode material.
[0119] Comparing Examples 1 to 3 and Comparative Example 2, 0.1 < 7a is satisfied. 2 b / (10(1-a) 2 ×c×d)<1.1 can take into account both higher capacity and lower expansion.
[0120] Example 4
[0121] Referring to the above gram capacity experiment, the difference is that the metal sodium sheet is used as the positive electrode, the electrolyte in the electrolyte is 1mol / LNaPF6, the negative electrode sheet and the separator are the same, and they are assembled into a sodium ion buckle battery. The gram capacity is measured, and the results show that it can reach more than 1500mAh / g; the first efficiency is measured, and the results show that it can reach more than 90%.
[0122] The present application is described in detail above in conjunction with the embodiments, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
Claims
1. A composite material, characterized in that The composite material comprises: A porous carbon skeleton, wherein nano red phosphorus is attached to the porous carbon skeleton; A carbon coating layer is coated on the surface of the porous carbon skeleton.
2. The composite material according to claim 1, characterized in that The porosity of the porous carbon skeleton is greater than 40%.
3. The composite material according to claim 1, characterized in that The mass percentage of the nano red phosphorus in the porous carbon skeleton is more than 50%.
4. The composite material according to claim 1, characterized in that The composite material satisfies 0.1<7a 2 b / (10(1-a) 2 ×c×d)<1.1; wherein a is the mass percentage of the nano red phosphorus in the porous carbon skeleton; b is the average particle size D of the nano red phosphorus V 50, in μm; c is the average particle size D of the porous carbon skeleton V 50, unit is μm; d is the porosity of the porous carbon skeleton.
5. The composite material according to claim 4, characterized in that The average particle size D of the porous carbon skeleton V 50 is 2 to 50 μm, and the average particle size D of the nano red phosphorus is V 50 is 1~1000nm.
6. The method for preparing the composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S100: mixing red phosphorus, a first carbon source and a self-sacrificial template, pressurizing and heating to 100-200° C. under a protective atmosphere to obtain a mixed solid; S200: heating the mixed solid to 250-400° C. to crush it into mixed particles; S300: mixing the mixed particles with a second carbon source, and carbonizing at 420-500° C. to obtain an intermediate; S400: Cooling the intermediate to 240-280° C. to obtain the composite material.
7. The preparation method according to claim 6, characterized in that: The self-sacrificial template includes at least one of polystyrene, polymethyl methacrylate, and polyetherimide; and / or, the first carbon source includes at least one of graphite and hard carbon; and / or, the second carbon source includes at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, melamine resin, polybutadiene resin, polydopamine, citric acid, glucose, fructose, sucrose, maltose, dextrin, starch, sorbitol, tartaric acid, ethylenediaminetetraacetic acid, polyethylene glycol, polyvinyl alcohol, polyvinyl butyral, polyacrylic acid, carboxymethyl cellulose, coal tar pitch, and needle tar pitch.
8. The preparation method according to claim 6, characterized in that: The pressure condition of the pressurization treatment is 2 to 6 kPa.
9. A secondary battery, characterized in that: The composite material comprises the composite material according to any one of claims 1 to 5.
10. Electrical equipment, characterized in that: A secondary battery comprising the secondary battery according to claim 9.
Citation Information
Patent Citations
Phosphorus-carbon composite material and preparation method and application thereof
CN105702939A
Phosphorus-carbon composite material and preparation method therefor, and battery applying phosphorus-carbon composite material
CN107681126A
Phosphorus-based negative electrode material and preparation method thereof, negative electrode and lithium ion battery
CN109216682A
Negative electrode composite material and preparation method thereof, negative electrode pole piece and battery
CN116759529A
Negative electrode composite material and preparation method thereof, negative electrode pole piece and battery
CN116759564A